2020
DOI: 10.1093/neuonc/noaa191
|View full text |Cite
|
Sign up to set email alerts
|

Reduced chromatin binding of MYC is a key effect of HDAC inhibition in MYC amplified medulloblastoma

Abstract: Background The sensitivity of MYC amplified medulloblastoma to class I HDAC inhibition has been shown previously, however understanding the underlying molecular mechanism is crucial for selection of effective HDAC inhibitors for clinical use. The aim of this study was to investigate the direct molecular interaction of MYC and the class I HDAC2, and the impact of class I HDAC inhibition on MYC function. Methods Co-immunoprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…As MYC and MYCN are frequently amplified and overexpressed in the three tumor types investigated in this screen, it will be important to further investigate the precise role of these factors in the treatment response. The HDACi entinostat was shown to inhibit MYC transcriptional activity in MYC amplified MB 21 , in line with the downregulation of MYC target genes observed here upon combination treatment. Interestingly, a previous study identified HDAC and Pi3K antagonists to inhibit MYC-driven medulloblastoma 19 .…”
Section: Discussionsupporting
confidence: 82%
“…As MYC and MYCN are frequently amplified and overexpressed in the three tumor types investigated in this screen, it will be important to further investigate the precise role of these factors in the treatment response. The HDACi entinostat was shown to inhibit MYC transcriptional activity in MYC amplified MB 21 , in line with the downregulation of MYC target genes observed here upon combination treatment. Interestingly, a previous study identified HDAC and Pi3K antagonists to inhibit MYC-driven medulloblastoma 19 .…”
Section: Discussionsupporting
confidence: 82%
“…However, inhibitors of HDAC, but not sirtuins, increased the acetylation of c-Myc at lysine 323 and inhibited tumorigenesis [ 88 ], which promoted the association of c-Myc with Max, a partner required for c-Myc activation. HDAC inhibitors downregulated c-Myc by blocking GSK-3 phosphorylation and exhibited synergistic cytotoxic and c-Myc-suppressive effects ( Figure 4 ) [ 89 ]. HDAC3 also deacetylated c-Myc at lysine 323 in cholangiocarcinoma cells, which protected the protein from ubiquitin-dependent proteolysis [ 90 ].…”
Section: C-mycmentioning
confidence: 99%
“…Genomics Browser (IGV 2.8.9, released January 2020) was used for displaying and visualizing next generational sequencing data. For Myc's binding to histone genes in MB tumors, ChIP-seq data were obtained from the recently published study (GSE143386: GSM4257878_MB1, GSM4257882_MB2 and GSM4257886_MB3) 30 . For all images illustrating the nascent RNA, the numbers of reads uniquely mapped to the genome were used for data range normalization when the IGV images were generated.…”
Section: Visualization Of Chip-seq and Rna-seq Data And Gene Set Enrichment Analysis Integrativementioning
confidence: 99%
“…4b). To further define the regulatory role of Myc in the expression of the histone genes, we analyzed previously reported ChIP-seq data in Myc-driven MBs 30 . The analysis revealed Myc's binding to all histone genes that were detected in the nascent RNA-seq (Fig.…”
mentioning
confidence: 99%